2(-5-6x)=-46

Simple and best practice solution for 2(-5-6x)=-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-5-6x)=-46 equation:


Simplifying
2(-5 + -6x) = -46
(-5 * 2 + -6x * 2) = -46
(-10 + -12x) = -46

Solving
-10 + -12x = -46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -12x = -46 + 10

Combine like terms: -10 + 10 = 0
0 + -12x = -46 + 10
-12x = -46 + 10

Combine like terms: -46 + 10 = -36
-12x = -36

Divide each side by '-12'.
x = 3

Simplifying
x = 3

See similar equations:

| 7b+-15=5b+-3 | | 11-2*3/5=0 | | -8(u-1)=-4u+12 | | 6x+24x-9=6(5x+5) | | F(x)=sqrt(x+3) | | 4.10(x-5)=-80 | | 420n^4-708n^3+168n^2=0 | | 1/3x^11x-4=0 | | 3x+2y+4z=9 | | ln(2x+3x^2)=3 | | 5(-2x-8)=-30 | | 2.7(x+8)=49 | | 70n^4-118n^3+28n^2=0 | | -3+7x=-x+93 | | X-2b= | | 209x-152=19(11x-8) | | 7m-4=11 | | -5x-2=-24+6x | | 5(20-1.6x)=100 | | 5y+8x=100 | | 65x/8 | | x+8=-4x+68 | | 8w/8=65x/8 | | 400=14.814x+6.8 | | 6x+8=-7x-109 | | n/8​​=​11/5​​ | | 18(t-6)+3t=7(3t+4)-8 | | 3x-94=36x+38 | | 2t^3-3t+1=0 | | 3v^3+21v^2-54v=0 | | x-6=-7x-30 | | Y=4x^3+x-5 |

Equations solver categories